2022
DOI: 10.3389/fchem.2022.917511
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Characteristics and Charge Transfer Kinetics of Fluoride in Water by Different Adsorbents

Abstract: Water containing high concentrations of fluoride is widely distributed and seriously harmful, largely because long-term exposure to fluoride exceeding the recommended level will lead to fluorosis of teeth and bones. Therefore, it is imperative to develop cost-effective and environmentally friendly adsorbents to remove fluoride from polluted water sources. In this study, diatomite (DA), calcium bentonite (CB), bamboo charcoal (BC), and rice husk biochar (RHB) were tested as adsorbents to adsorb fluoride (F‐) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Kumar et al [30] used biochar produced from peanut residues and obtained the removal of 3.66 mg•g −1 of fluoride. Similar values, 6.58 mg•g −1 and 3.42 mg•g −1 , were achieved with biochar produced from bamboo and rice husks, respectively [31], and Sadhu et al [10] removed 9.5 mg•g −1 of fluoride in groundwater samples using biochar produced from watermelon rind.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Kumar et al [30] used biochar produced from peanut residues and obtained the removal of 3.66 mg•g −1 of fluoride. Similar values, 6.58 mg•g −1 and 3.42 mg•g −1 , were achieved with biochar produced from bamboo and rice husks, respectively [31], and Sadhu et al [10] removed 9.5 mg•g −1 of fluoride in groundwater samples using biochar produced from watermelon rind.…”
Section: Introductionsupporting
confidence: 59%
“…These functional groups exhibit stronger interactions with fluoride ions [77]. Peaks around 1600 cm −1 may be attributed to water bonds or hydroxyl groups present on the surface [31].…”
Section: Physicochemical Characterization Of Bcmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al [ 20 ] found that the hydrothermal modified fly ash showed maximum fluorine adsorption capacity of 47.35 mg/g when employed to remove fluorine in waste water under alkaline conditions. Fluorine adsorption capacities of 6.58 mg/g and 3.42 mg/g were achieved with biochar produced from bamboo and rice husks, respectively [ 21 ], and Sadhu et al [ 22 ] showed fluoride removal capacity of 9.5 mg/g for groundwater samples using biochar produced from watermelon rind.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyapatite, Ca 10 (PO 4 ) 6 (OH) 2 (HAP) as calcium phosphate-based bioceramics is widely used in biotechnology and medical applications to repair damaged parts of the body as an implant. HAP as an adsorbent has demonstrated comparatively good defluoridation performance in several studies (Bhatnagar et al, 2011;Tang et al, 2022). Previous studies have demonstrated that the HAP's surface hydroxyl groups are an active site for adsorption.…”
Section: Introductionmentioning
confidence: 99%